Ethical considerations of AI through a socio-technical lens: insights from ELT context as a higher education system - M. Pınar Babanoğlu; Tuçe Öztürk Karataş; Esin Dündar (Cogent Education)
In the twenty-first century, future teachers should be well prepared for the challenges of AI and the significant opportunities provided by its ethical use. AI has penetrated those fields and brought digital transformation at both the micro and the macro levels. Students and teachers are not immune to its deep impacts. Thus, with a socio-technical stance, this study, designed with a qualitative descriptive approach, is one that has delved into the ethical conceptions of AI from the perspectives of 252 English language teacher education (ELT) students who are future English teachers in Türkiye. The findings indicated four main coding units (1) Distrust in AI, (2) Blind Trust in AI, (3) Ethical use of AI and (4) Unethical use of AI. The views of the included students reflected black-box effects through distrust and techno-over-reliance with blind-trust, as well as the use of AI for the well-being of students and for life-long learning. Implications of the current study address AI embracing ethics as a part of ELT contexts and higher education systems in a socially responsible manner for more inclusive and sustainable digital futures for society and human agency.